A review of recent advancements in soft and flexible robots for medical applications - Zhang, Yongde; Lu, Mingyue (The international journal of medical robotics + computer assisted surgery, 2020)
Background Soft and flexible robots for medical applications are needed to change their flexibility over a wide range to perform tasks adequately. The mechanism and theory of flexibility has been a scientific issue and is of interest to the community. Methods Recent advancements of bionics, flexible actuation, sensing, and intelligent control algorithms as well as tunable stiffness have been referenced when soft and flexible robots are developed. The benefits and limitations of these relevant studies and how they affect the flexibility are discussed, and possible research directions are explored. Results The bionic materials and structures that demonstrate the potential capabilities of the soft medical robot flexibility are the fundamental guarantee for clinical medical applications. Flexible actuation that used to provide power, intelligent control algorithms which are the exact executors, and the wide range stiffness of the soft materials are the three important influence factors for soft medical robots. Conclusion Some reasonable suggestions and possible solutions for soft and flexible medical robots are proposed, including novel materials, flexible actuation concepts with a built‐in source of energy or power, programmable flexibility, and adjustable stiffness.